2009
DOI: 10.1897/08-135r.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photosystem II inhibitors and their mixture on freshwater phytoplankton succession in outdoor mesocosms

Abstract: Effects of three photosystem II inhibitors and of their mixture on a freshwater phytoplankton community were studied in outdoor mesocosms. Atrazine, isoproturon, and diuron were applied as 30% hazardous concentrations (HC30s) obtained from species-sensitivity distributions. Taking concentration addition into account, the mixture comprised one-third of the HC30 of each substance. Effects were investigated during a five-week period of constant concentrations and a five-month posttreatment period when the herbici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 35 publications
4
19
0
1
Order By: Relevance
“…We consider however more likely that the low exposure level and the very short time characterising our exposure design were not sufficient to induce disappearance of an entire functional group over the course of 2-3 generations. This idea is supported by previous studies: treatment of phytoplankton communities in outdoor mesocosms with herbicides, for example, resulted in limited effects on biodiversity after short periods of time, with many treatments increasing Shannon diversity for longer exposure time (Knauert et al 2009). A positive control, with a known effect on community biodiversity, would have allowed to directly test the importance of methodological constraints in detecting extinction of one or more functional groups and, although challenging, should be included in future similar studies, also to assess the impact of extinction on inferred community effects.…”
Section: Community Effects Of Tcssupporting
confidence: 65%
See 1 more Smart Citation
“…We consider however more likely that the low exposure level and the very short time characterising our exposure design were not sufficient to induce disappearance of an entire functional group over the course of 2-3 generations. This idea is supported by previous studies: treatment of phytoplankton communities in outdoor mesocosms with herbicides, for example, resulted in limited effects on biodiversity after short periods of time, with many treatments increasing Shannon diversity for longer exposure time (Knauert et al 2009). A positive control, with a known effect on community biodiversity, would have allowed to directly test the importance of methodological constraints in detecting extinction of one or more functional groups and, although challenging, should be included in future similar studies, also to assess the impact of extinction on inferred community effects.…”
Section: Community Effects Of Tcssupporting
confidence: 65%
“…More experimental studies should address in the future the relative importance and interaction of physiological acclimation, evolutionary processes and ecological dynamics in explaining community effects of micropollutants like TCS, in order to scale the effects of stressors through community level dynamics and link between response-and-effect traits (the Price equation is only one of the possible ways forward in this direction). The study of resilience and recovery time in complex natural systems also appears critical, especially after exposure to mixtures that may affect the structure and functioning of communities more deeply and unpredictably (Knauert et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Knauert et al [39] concluded that CA is applicable for both effects on photosynthesis as well as higher-order ecological effects such as total abundance and diversity [20] in a phytoplankton community after exposure to non-congeneric PSII inhibitors at the level of HC30. We now may conclude that this phenomenon is not restricted to a single effect level.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplankton responses to contaminants can, for example, be influenced by species interactions (Leboulanger et al, 2001;Ortmann et al, 2012), grazing pressure (Munoz et al, 2001), temperature (BĂ©rard et al, 1999), water chemistry (Knauer et al, 2007), light exposure history (Guasch and Sabater, 1998;Laviale et al, 2010) or contamination exposure history (Dorigo et al, 2004;Serra et al, 2009). In addition, in its natural environment, phytoplankton is exposed to contaminant mixtures and, depending on the mixture, additive, synergistic or antagonistic effects may result from contaminant interactions (DeLorenzo and Fleming, 2008;Knauert et al, 2009;Relyea, 2009).…”
Section: Introductionmentioning
confidence: 99%